Development of LULABLOCKS: Textured Color Blocks to Enhance Fine Motor Skills in Children Aged 4–6 Years - Leli Nurlaeli; Nita Priyanti; Debie Susanti (Kirana Publisher (KNPub), 2026)
This study aimed to develop textured color smart blocks called “LULABLOCKS” and examine their feasibility and effectiveness in improving fine motor skills in children aged 4–6 years. The study employed the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 40 children aged 4–6 years at TK Trisula Perwari, Purwakarta Regency. Data were collected through observations, interviews, expert validation, and fine motor skill assessments using pre-test and post-test measurements. The results of the study indicate that: (1) the LULABLOCKS textured color smart blocks were successfully developed with key features including texture variations, interlocking connection systems, diverse colors and shapes, and comprehensive usage guidelines; (2) expert validation results showed an average feasibility score of 88.8% (very valid category), with the highest score obtained in the aspect of usefulness for fine motor skill development (100%); and (3) there was a significant improvement in children's fine motor skills, increasing from an average score of 2.11 (52.6%) in the pre-test to 3.29 (82.2%) in the post-test, representing an improvement of 29.6%, with statistical significance indicated by t-count 18.72 > t-table 2.02 (p < 0.05). The 4–6 years age group showed the highest improvement (30.7%). Teacher and student responses were highly positive, with an acceptance level exceeding 80%. In conclusion, the LULABLOCKS textured color smart blocks are valid, practical, and effective in improving fine motor skills in early childhood, particularly in the aspects of grasping and manipulating small objects.